Application of IR and NMR spectroscopy to certain complexes of 8-hydroxyquinoline and 8-aminoquinoline - Knight, Cheryl Lynn (Department of Chemistry, 2016)
The IR spectra of twenty-one transition metal complexes of 8-hydroxyquinoline over the range 700 - 50 cm⁻¹ are discussed in relation to their known or inferred structures. The complexes are of three types: (a) the bis(aquo) complexes of the first row transition metal(II) ions, [M(ox)₂(H₂O)₂] (M =Mn, Fe, Co, Ni, Cu, Zn); (b) the corresponding anhydrous complexes, [M(ox)₂]n (M=Mn, Co, Ni, Cu, Zn) and (c) the complexes of the metal(III) ions, [M(ox)₃] (M = Sc, V, Cr, Mn, Fe, Co, Ga, Rh and In). Deuterated 8-hydroxyquinoline was. synthesized by the Skraup synthesis and has been used to assist in the assignment of the metal-ligand modes. The assignment of these bands was further based on ⁶⁴,⁶⁸Zn labellihg of the bis(aquo) zinc chelate and on the effects of metal ion substitution in relation to structural considerations based on crystal field theory. An investigation of the IR spectra of a series of -tris, bis and mono(8-aminoquinoline) complexes of the first transition row metal(II) perchlorates and halides is reported.